Penerapan Profesionalisme oleh Guru Matematika dalam Mengelola Proses Pembelajaran di UPT SMP Negeri 35 Medan - Sari, Sri Nila; Kamila, Rahma; Pakpahan, Siti Ramadhani; Siregar, Fatma Wati (Yayasan Amanah Nur Aman, 2025)
This study examines the implementation of mathematics teacher professionalism at UPT SMP Negeri 35 Medan. Using a descriptive qualitative approach, the study explores how mathematics teacher plan, implement, and evaluate learning. Interview results show that teacher demonstrate professionalism through well-prepared lesson plans (RPP), mastery of subbject matter, use of varied teaching methods and media, and the ability to create a conducive classroom atmosphere. The main clallenges include a lack of student interest and limited school facilities. Nevertheless, teacher continue to make optimal efforts through personal approaches and assess success based on student’s understanding and comfort. Teacher professionalism, reflected in their discipline and sense of responsibility, plays a crucial role in improving the quality of mathematics learning.